Modified CM square electric power corrugated pipe
By using modified CM materials and composite fillers in square power corrugated pipes, the problems of insufficient burn-through performance and mechanical strength in the prior art are solved, and multiple performance improvements of the material are achieved.
Patent Information
- Application Number
- CN202411733145.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing square electric corrugated pipes have shortcomings in their burn-through resistance and mechanical strength, and it is difficult to improve their performance at the same time.
Square power corrugated tube made of modified CM material optimizes the surface properties and composition of the filler to improve the compatibility and overall strength of the material by introducing polysiloxane segments into chlorinated polyethylene rubber and using a composite filler composed of modified inorganic powder and modified glass microbeads.
The tensile performance, impact resistance, burn-through resistance and low temperature resistance of modified CM square power corrugated pipes are significantly improved, ensuring that the material maintains stable performance in complex environments.
Smart Images

Figure CN119505451A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electric power pipe processing, and in particular to a modified CM square electric power corrugated pipe. Background Art
[0002] In the power system, corrugated pipes, as an important pipe material, are widely used in the protection and laying of power cables. With the development of the power industry and the advancement of technology, the performance requirements for corrugated pipes are getting higher and higher; CM material, namely chlorinated polyethylene rubber, is a saturated thermoplastic elastomer that can maintain stable performance in various harsh environments. The square power tube is a cable protection tube with a rectangular structure, which is mainly designed to solve the problems of traditional circular corrugated tubes that are difficult to fix, difficult to connect, and have low laying efficiency.
[0003] In recent years, the application of modified materials in the manufacture of corrugated pipes has gradually increased. Modified materials can give corrugated pipes better performance by adjusting the formula and process, such as higher strength, better heat resistance, higher flame retardancy, etc. Modified CM materials have excellent elasticity, wear resistance and corrosion resistance, and can meet the use requirements of power corrugated pipes in complex environments; Traditional electric bellows are usually stacked in rows. When a fire occurs in any of the electric bellows, it is easy to burn through the adjacent electric bellows. In order to improve the burn-through resistance of the electric tube, inorganic fillers are usually added to the flame retardant material and a support system is constructed in the electric bellows. However, due to the compatibility of molecules, the mechanical strength of the electric bellows will show a significant decrease after the addition of inorganic fillers.
[0004] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0005] The object of the present invention is to provide a modified CM square power bellows, which is used to solve the technical problem that the burn-through resistance and mechanical strength of the square power bellows in the prior art need to be further improved.
[0006] The object of the present invention can be achieved by the following technical scheme: a modified CM square power corrugated pipe, comprising a square pipe and a plurality of corrugated rings arranged outside the square pipe, wherein the square pipe and the corrugated rings are both made of modified CM material; Two adjacent side edges of the corrugated ring are provided with arc grooves.
[0007] Further, the modified CM material is processed by the following steps: A1. Add chlorinated polyvinyl chloride, modified chlorinated polyethylene rubber and additives to an internal mixer at a temperature of 170-180° C., keep warm and mix for 10-15 minutes, add vinyl triethoxysilane to the internal mixer in batches, keep warm and mix for 5-8 minutes, add composite fillers to the internal mixer in batches, keep warm and mix for 20-30 minutes, cool and discharge, and crush to obtain a modified CM precursor, wherein the composite filler is composed of modified inorganic powder and modified glass microspheres in a weight ratio of 5-6:3-4; A2, after uniformly mixing the modified CM precursor, ammonium carbonate and vulcanization accelerator, adding them into a twin-screw extruder, molten extrude into a molding die, cool and solidify, and the green body is modified CM green body; A3. Place the modified CM blank in a vulcanizing tank, vulcanize it under heat preservation to obtain a modified CM material.
[0008] Furthermore, one end of the square tube is provided with a clamping section, and the other end of the square tube is provided with a clamping groove corresponding to the clamping section.
[0009] Furthermore, in step A1, the weight ratio of the chlorinated polyvinyl chloride, modified chlorinated polyethylene rubber, additive, vinyl triethoxy silane and composite filler is 90-100:25-30:5-7:8-12:50-60, the composite filler is composed of modified inorganic powder and modified glass microspheres in a weight ratio of 5-6:3-4, the additive is composed of initiator, dispersant, antioxidant, plasticizer and lubricant in a weight ratio of 10:3:4:5:3, the initiator is diisopropylbenzene peroxide, the dispersant is stearate, the antioxidant is one of antioxidant 1010, antioxidant 168, and antioxidant 626, the plasticizer is phthalate, and the lubricant is oleamide.
[0010] Furthermore, in step A2, the weight ratio of the modified CM precursor, ammonium carbonate and the vulcanization aid is 100:8-10:4-6, the vulcanization aid is composed of dicumyl peroxide, vulcanizing agent TDDS and accelerator 808 in a weight ratio of 2:4:1, and the temperatures of the six temperature zones from the feed end to the discharge end of the twin-screw extruder are 260°C, 265°C, 265°C, 265°C, 265°C, and 270°C, respectively, and the screw speed of the twin-screw extruder is 18r / min.
[0011] Furthermore, in step A3, the temperature of the vulcanization tank is 160-170° C., the pressure is 1.2-1.5 MPa, and the vulcanization time is 30-40 min.
[0012] Further, the modified chlorinated polyethylene rubber is processed by the following steps: B1. Hexamethyl-1,15-dihydroxyoctasiloxane and acetone are added to a nitrogen-protected reactor and stirred. Isocyanatepropyltriethoxysilane is added to the reactor. The temperature of the reactor is raised to reflux, and the reaction is carried out for 60-80 minutes. The modified polysiloxane is obtained by post-treatment. The synthetic reaction mechanism of modified polysiloxane is: The hydroxyl groups on the hexadecyl-1,15-dihydroxyoctasiloxane molecule are used as active reaction sites, and the isocyanate group undergoes a condensation reaction with the hydroxyl group to replace the hydroxyl groups on the hexadecyl-1,15-dihydroxyoctasiloxane, forming triethoxysilane modifications at both ends of the siloxane chain segment to prepare modified polysiloxane.
[0013] B2. Add chlorinated polyethylene rubber, modified polysiloxane, tetraethyl orthosilicate and emulsion into a high-speed dispersing emulsifier, and then transfer to a reactor for stirring. The temperature of the reactor is increased to 70-80°C. Hydrochloric acid is added to the reactor to adjust the pH value of the system to 2-3. The reaction is kept warm for 2-3 hours, and the modified chlorinated polyethylene rubber is obtained by post-treatment.
[0014] The synthetic reaction mechanism of modified chlorinated polyvinyl chloride rubber is: Under the action of a high-speed dispersing emulsifier, chlorinated polyethylene rubber, modified polysiloxane and tetraethyl orthosilicate are emulsified into fine droplets through high-speed shearing and impact, and are evenly dispersed in the emulsion. The pH of the reaction system is adjusted by hydrochloric acid to promote the hydrolysis and recombination of the siloxane bonds on the modified polysiloxane and tetraethyl orthosilicate molecules, to form a complex polysiloxane cross-linking structure on the surface of the chlorinated polyethylene rubber material, to promote the uniform mixing of polysiloxane and chlorinated polyvinyl chloride rubber, and to prepare modified chlorinated polyethylene rubber doped with polysiloxane.
[0015] Furthermore, in step B1, the usage ratio of hexadecyl-1,15-dihydroxyoctasiloxane and isocyanatepropyltriethoxysilane is 1 mol:2 mol, the usage ratio of hexadecyl-1,15-dihydroxyoctasiloxane and acetone is 1 g:10 mL, and the post-treatment includes: after the reaction is completed, distilling off the solvent under reduced pressure to obtain modified polysiloxane.
[0016] Furthermore, in step B2, the amount ratio of the chlorinated polyethylene rubber, modified polysiloxane, tetraethyl orthosilicate, and emulsion is 8-10g:1-2g:0.8-1.2g:50mL, and the emulsion is composed of purified water, polyethylene glycol 400, and sodium dodecylbenzene sulfonate in an amount ratio of 100mL:7g:2g. The post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, centrifuged, the solid is washed with purified water to neutrality, and then transferred to a drying oven at a temperature of 70-80°C, and vacuum dried to constant weight to obtain modified chlorinated polyethylene rubber.
[0017] Further, the modified inorganic powder is processed by the following steps: C1. Mixing attapulgite and kaolin to form an inorganic mixed powder; C2, adding the inorganic mixed powder, purified water and dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride into a reactor, ultrasonically dispersing for 30-50 min, raising the temperature of the reactor to 67-75° C., adding sodium hydroxide solution into the reactor, keeping the temperature and ultrasonically dispersing for 60-80 min, and post-treating to obtain intermediate I; C3. Add intermediate I and methanol solution into a reactor, and disperse them by ultrasonic for 40-50 min. Add sodium sulfate of nonylphenol polyoxyethylene ether (10) into the reactor, and disperse them by ultrasonic for 6-8 h at room temperature. Post-treat to obtain modified inorganic powder.
[0018] The synthetic reaction mechanism of modified inorganic powder is: After the inorganic mixed powder, purified water and dimethyl octadecyl [3-(trimethoxysilyl) propyl] ammonium chloride are uniformly mixed by ultrasonic dispersion, the siloxane bonds on the dimethyl octadecyl [3-(trimethoxysilyl) propyl] ammonium chloride molecules are hydrolyzed and react with the active sites on the surface of the inorganic mixed powder under the catalytic action of the base to form chemical crosslinks, and the dimethyl octadecyl ammonium chloride is modified on the surface of the inorganic mixed powder to prepare the intermediate I; As a surfactant, sodium nonylphenol polyoxyethylene ether (10) sulfate has excellent dispersing and emulsifying properties. It can interact with the active groups on the surface of the modified inorganic powder precursor to further improve the dispersibility and stability of the inorganic powder. In addition, when sodium nonylphenol polyoxyethylene ether (10) sulfate is used in excess, the sulfate ions on the sodium nonylphenol polyoxyethylene ether (10) sulfate molecules replace the chloride ions in the ammonium chloride salt to form ionic bonds, thereby being loaded on the surface of the inorganic powder to prepare the modified inorganic powder.
[0019] Furthermore, in step C1, the weight ratio of the attapulgite and kaolin is 3:2; in step C2, the amount ratio of the inorganic mixed powder, purified water, dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride and sodium hydroxide solution is 7g:40mL:3g:10mL, and the concentration of the sodium hydroxide solution is 1-2mol / L. The post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed with purified water until it is neutral and then dried, and the filter cake is transferred to a drying oven at a temperature of 70-80°C and dried to constant weight to obtain intermediate I.
[0020] Furthermore, in step C3, the amount ratio of the intermediate I, the methanol solution and the sodium sulfate of nonylphenol polyoxyethylene ether (10) is 10g:100mL:10g, the methanol solution is composed of anhydrous methanol and purified water in a volume ratio of 3:2, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed with purified water until it is neutral and then dried, the filter cake is transferred to a drying oven at a temperature of 70-80°C, and dried to constant weight to obtain a modified inorganic powder.
[0021] Further, the modified glass microspheres are processed by the following steps: D1. Add hollow glass microspheres and activation solution into a reaction kettle and stir. Raise the temperature of the reaction kettle to 70-80°C, keep warm and stir for 40-50 minutes, and perform post-treatment to obtain activated microspheres. D2. Add activated microbeads, 7-octenyltrimethoxysilane and anhydrous ethanol into a reactor and stir. Increase the temperature of the reactor to 50-60° C., add sodium hydroxide solution into the reactor, keep the temperature for 80-100 minutes, and perform post-treatment to obtain modified glass microbeads.
[0022] The synthetic reaction mechanism of modified glass microspheres is: The activation solution composed of hydrofluoric acid and nitric acid can etch the surface of the hollow glass microspheres while cleaning them, forming more silanol groups on the surface of the hollow glass microspheres. The activated microspheres are surface-modified with 7-octenyltrimethoxysilane in an alkaline environment to prepare modified glass microspheres with a large number of unsaturated double bonds on the surface.
[0023] Furthermore, in step D1, the hollow glass microspheres and the activation solution are used in a ratio of 1 g:7 mL, the activation solution is composed of hydrofluoric acid, 50 wt% nitric acid and purified water in a ratio of 0.5 mL:30 mL:50 mL, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed with purified water until it is neutral and then dried, the filter cake is transferred to a drying oven at a temperature of 70-80 ° C, and dried to constant weight to obtain activated microspheres.
[0024] Furthermore, in step D2, the amount ratio of the activated microbeads, 7-octenyltrimethoxysilane, anhydrous ethanol and sodium hydroxide solution is 5g:2g:30mL:8mL, the concentration of the sodium hydroxide solution is 0.5-1.5mol / L, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed with purified water until it is neutral and then dried, the filter cake is transferred to a drying oven at a temperature of 65-75°C, and vacuum dried to constant weight to obtain modified glass microbeads.
[0025] The present invention has the following beneficial effects: 1. The modified CM square power bellows of the present invention is a modified chlorinated polyethylene rubber and chlorinated polyvinyl chloride combined mixed matrix reinforced by siloxane, and a composite filler composed of modified inorganic powder and modified glass microspheres is used to reinforce the mixed matrix to prepare the modified CM square power bellows. The hollow glass microspheres are activated and surface-modified and then mixed with the modified inorganic powder to prepare the composite filler, and the surface properties and composition of the filler are optimized so that the composite filler is evenly dispersed in the power bellows material, the compatibility of the composite filler and the mixed matrix is improved, the weak interface of the material is reduced, and a composite system of heat insulation and burn-through resistance is constructed. In melt casting, ammonium carbonate is used as a porogen to form dense pores in the melt casting system. Through vulcanization treatment, the degree of cross-linking between molecules is increased, so that chemical bonds are formed between the power bellows materials and a cross-linking structure is formed between the molecules, thereby improving the overall strength and rigidity of the material. By optimizing the structure of the power bellows, with the square as the main body and the structure of the corrugated ring optimized, the power bellows can be evenly laid and stacked neatly, and a filling gap can be formed between the power bellows. By filling the filling gap with materials such as mud and sand, the independence of each power tube can be promoted, thereby avoiding the impact of the power tube burning through on the adjacent cables in case of fire.
[0026] 2. The modified CM square power bellows of the present invention is modified by introducing polysiloxane segments into chlorinated polyethylene rubber. The polysiloxane segments with unique flexibility and low surface energy characteristics are introduced on the basis of chlorinated polyethylene rubber to improve the flexibility of the chlorinated polyethylene rubber material. The electronegativity difference between silicon atoms and oxygen atoms in the polysiloxane segments makes the segments partially have a certain polarity, so that the modified chlorinated polyethylene rubber and the chlorinated polyvinyl chloride molecules form a dipole-dipole interaction, thereby enhancing the interaction between the modified chlorinated polyethylene rubber and the chlorinated polyvinyl chloride molecules. The interface bonding force can improve the tensile properties and impact resistance of the power corrugated tube. The introduction of polysiloxane chain segments can also enable the composite material to maintain good flexibility and elasticity at low temperatures, resist hardening and embrittlement caused by low temperatures, thereby improving its low temperature resistance. Both modified chlorinated polyethylene rubber and chlorinated polyvinyl chloride have high thermal stability and flame retardant properties, which can effectively slow down the transfer of heat and the spread of flames. The polysiloxane chain segments introduced into the material can form a carbon layer at high temperatures, further preventing the transfer of heat and the spread of flames, and increasing the burn-through time of the cable corrugated tube.
[0027] 3. The modified CM square power bellows of the present invention is treated with dimethyl octadecyl [3-(trimethoxysilyl)propyl] ammonium chloride to treat attapulgite and kaolin. The long-chain alkyl part has hydrophobicity, which can improve the surface properties of inorganic particles and make them more lipophilic, thereby improving the compatibility with modified chlorinated polyethylene rubber and chlorinated polyvinyl chloride, reducing the interfacial tension between the polymer matrix, and facilitating the uniform dispersion and stable existence of inorganic particles in the polymer matrix. The unsaturated double bonds modified on the surface of the modified glass microspheres can serve as active groups and cross-link with halogens during the vulcanization process. , improve the degree of cross-linking between molecules, the composite filler is filled in the mixture as a rigid particle, which can support the entire structure like a "skeleton", thereby increasing the tensile yield stress, and the modified glass microspheres can absorb and disperse the impact energy, help disperse the stress, reduce the expansion and damage of the cracks, thereby improving the overall impact resistance. Hollow glass microspheres are an inorganic material with high melting point, low thermal conductivity and non-flammable properties. Due to its non-flammability, it can form a heat-insulating layer on the surface of the mixture with the modified inorganic powder to prevent heat from transferring to the inside, slow down the penetration of the flame into the mixture, and thus prolong the burn-through time. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 It is a schematic diagram of the three-dimensional structure of the power bellows of the present invention; Figure 2 It is a schematic diagram of the end face truncation structure of the power bellows of the present invention; Figure 3 It is a schematic diagram of stacking several cable corrugated tubes of the present invention.
[0030] In the figure: 100, square tube; 101, clamping section; 102, clamping groove; 200, corrugated ring; 201, arc groove. DETAILED DESCRIPTION
[0031] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] The chlorine content of the chlorinated polyethylene rubber in this application is 30-40%; The chlorination degree of the chlorinated polyvinyl chloride in this application is 35-40%. Example 1
[0033] See also Figure 1-Figure 3 A modified CM square power corrugated tube of this embodiment includes a square tube 100 and a plurality of corrugated rings 200 arranged outside the square tube 100, and the square tube 100 and the corrugated rings 200 are both made of modified CM material; The outer wall of the corrugated ring 200 is an arc-shaped structure, and arc grooves 201 are provided on two adjacent sides of the corrugated ring 200. The arc of the arc groove 201 is the same as the arc of the corrugated ring 200 protruding outward. The outer wall of the corrugated ring 200 and the side wall of the arc groove 201 are provided with mutually matching protrusions (not shown) and clamping grooves (not shown) to prevent the power bellows from slipping after stacking; A clamping section 101 is provided at one end of the square tube 100, and a clamping groove 102 corresponding to the clamping section 101 is provided at the other end of the square tube 100. The clamping section 101 is extended to the inside of the clamping groove 102, so as to facilitate the docking and extension of the power bellows. A circular hole (not shown in the figure) is provided on the clamping section 101, and a through hole (not shown in the figure) corresponding to the circular hole is provided at a position of the square tube 100 near the clamping groove 102, so as to facilitate the connection and fixation of the power bellows using a limit rivet. Example 2
[0034] A method for preparing a modified CM square power bellows in this embodiment comprises the following steps: S1. Preparation of modified chlorinated polyethylene rubber Weigh: 611.3 g of hexamethyl-1,15-dihydroxyoctasiloxane and 6113 mL of acetone, add them into a nitrogen-protected reactor and stir, add 494.7 g of isocyanatepropyltriethoxysilane into the reactor, raise the temperature of the reactor to reflux the system, react for 60 min, and evaporate the solvent under reduced pressure to obtain modified polysiloxane; Purified water, polyethylene glycol 400, and sodium dodecylbenzene sulfonate were mixed uniformly in a ratio of 100 mL:7 g:2 g to obtain an emulsion; Weigh: 800 g of chlorinated polyethylene rubber, 100 g of modified polysiloxane, 80 g of tetraethyl orthosilicate, and 5000 mL of emulsion, add them into a high-speed dispersing emulsifier, emulsify and disperse, then transfer them to a reactor for stirring, raise the temperature of the reactor to 70°C, add hydrochloric acid to the reactor, adjust the pH of the system to 2, keep the reaction warm for 2 hours, lower the temperature of the reactor to room temperature, centrifuge, wash the solid with purified water until it is neutral, transfer it to a drying oven at 70°C, and vacuum dry it to constant weight to obtain modified chlorinated polyethylene rubber.
[0035] S2. Preparation of modified inorganic powder The attapulgite and kaolin are mixed uniformly in a weight ratio of 3:2 to obtain an inorganic mixed powder; Weigh: 700 g of inorganic mixed powder, 4 L of purified water and 300 g of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride, add them to a reactor, ultrasonically disperse for 30 min, raise the temperature of the reactor to 67° C., add 1 L of 1 mol / L sodium hydroxide solution to the reactor, keep warm and ultrasonic for 60 min, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral and then drain, transfer the filter cake to a drying oven at 70° C., and dry to constant weight to obtain intermediate I; Anhydrous methanol and purified water were mixed uniformly in a volume ratio of 3:2 to obtain a methanol solution; Weigh: 500 g of intermediate I and 5 L of methanol solution are added to a reactor, ultrasonically dispersed for 40 min, 500 g of sodium sulfate of nonylphenol polyoxyethylene ether (10) is added to the reactor, and ultrasonically dispersed for 6 h at room temperature. The temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed with purified water until it is neutral and then dried, and the filter cake is transferred to a drying oven at a temperature of 70° C. and dried to constant weight to obtain a modified inorganic powder.
[0036] S3. Preparation of modified glass microspheres Mix hydrofluoric acid, 50 wt% nitric acid and purified water in a ratio of 0.5 mL:30 mL:50 mL to obtain an activation solution; Weigh: 500 g of hollow glass microspheres and 3.5 L of activation solution are added to a reactor and stirred. The temperature of the reactor is raised to 70°C, and the mixture is stirred for 40 min. The temperature of the reactor is lowered to room temperature, and the filter cake is filtered. The filter cake is washed with purified water until it is neutral and then dried. The filter cake is transferred to a drying oven at 70°C and dried to constant weight to obtain activated microspheres. Weigh: 500 g of activated microbeads, 200 g of 7-octenyltrimethoxysilane and 3 L of anhydrous ethanol, add them into a reactor and stir, raise the temperature of the reactor to 50°C, add 800 mL of 0.5 mol / L sodium hydroxide solution into the reactor, keep warm and react for 80 minutes, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral and then dry, transfer the filter cake to a drying oven at a temperature of 65°C, and vacuum dry it to constant weight to obtain modified glass microbeads.
[0037] S4. Preparation of modified CM materials The modified inorganic powder and the modified glass microspheres are uniformly mixed in a weight ratio of 5:3 to obtain a composite filler; Dicumyl peroxide, calcium stearate, antioxidant 1010, dibutyl phthalate and oleamide are uniformly mixed in a weight ratio of 10:3:4:5:3 to obtain an additive; Weigh: 9 kg of chlorinated polyvinyl chloride, 2.5 kg of modified chlorinated polyethylene rubber and 500 g of additives, add them to an internal mixer at a temperature of 170°C, keep warm and mix for 10 minutes, add 800 g of vinyl triethoxysilane to the internal mixer in batches, keep warm and mix for 5 minutes, add 5 kg of composite fillers to the internal mixer in batches, keep warm and mix for 20 minutes, cool down, discharge, and crush to obtain a modified CM precursor; Dicumyl peroxide, vulcanizing agent TDDS and accelerator 808 were uniformly mixed in a weight ratio of 2:4:1 to obtain a vulcanizing aid; Weigh: 10 kg of modified CM precursor, 800 g of ammonium carbonate and 400 g of vulcanizing agent, mix them evenly and add them into a twin-screw extruder, the temperatures of the 6 temperature sections from the feed end to the discharge end of the twin-screw extruder are 260° C., 265° C., 265° C., 265° C., 270° C., the screw speed of the twin-screw extruder is 18 r / min, and the twin-screw extruder is melt-extruded into a molding mold having the same molding cavity as the modified CM square power bellows provided in Example 1, and the temperature is reduced and solidified to obtain a modified CM blank; The modified CM blank was placed in a vulcanization tank with a temperature of 160°C and a pressure of 1.2 MPa. The vulcanization was carried out for 30 minutes to obtain a modified CM square power bellows. Example 3
[0038] A method for preparing a modified CM square power bellows in this embodiment comprises the following steps: S1. Preparation of modified chlorinated polyethylene rubber Weigh: 611.3 g of hexamethyl-1,15-dihydroxyoctasiloxane and 6113 mL of acetone, add them into a nitrogen-protected reactor and stir, add 494.7 g of isocyanatepropyltriethoxysilane into the reactor, raise the temperature of the reactor to reflux the system, react for 70 min, and evaporate the solvent under reduced pressure to obtain modified polysiloxane; Purified water, polyethylene glycol 400, and sodium dodecylbenzene sulfonate were mixed uniformly in a ratio of 100 mL:7 g:2 g to obtain an emulsion; Weigh: 900 g of chlorinated polyethylene rubber, 150 g of modified polysiloxane, 100 g of tetraethyl orthosilicate, and 5000 mL of emulsion, add them into a high-speed dispersing emulsifier, emulsify and disperse, then transfer to a reactor for stirring, raise the temperature of the reactor to 75°C, add hydrochloric acid to the reactor, adjust the pH of the system to 2.5, keep warm for 2.5 hours, lower the temperature of the reactor to room temperature, centrifuge, wash the solid with purified water until neutral, transfer to a drying oven at 75°C, and vacuum dry to constant weight to obtain modified chlorinated polyethylene rubber.
[0039] S2. Preparation of modified inorganic powder The attapulgite and kaolin are mixed uniformly in a weight ratio of 3:2 to obtain an inorganic mixed powder; Weigh: 700 g of inorganic mixed powder, 4 L of purified water and 300 g of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride, add them to a reactor, ultrasonically disperse for 40 min, raise the temperature of the reactor to 70°C, add 1 L of 1.5 mol / L sodium hydroxide solution to the reactor, keep warm and ultrasonic for 70 min, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral and then drain, transfer the filter cake to a drying oven at a temperature of 75°C, and dry to constant weight to obtain intermediate I; Anhydrous methanol and purified water were mixed uniformly in a volume ratio of 3:2 to obtain a methanol solution; Weigh: 500 g of intermediate I and 5 L of methanol solution are added to the reactor, ultrasonically dispersed for 45 min, 500 g of sodium sulfate of nonylphenol polyoxyethylene ether (10) is added to the reactor, and ultrasonically dispersed for 7 h at room temperature. The temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed with purified water until it is neutral and then dried, and the filter cake is transferred to a drying oven at a temperature of 75°C and dried to constant weight to obtain a modified inorganic powder.
[0040] S3. Preparation of modified glass microspheres Mix hydrofluoric acid, 50 wt% nitric acid and purified water in a ratio of 0.5 mL:30 mL:50 mL to obtain an activation solution; Weigh: 500 g of hollow glass microspheres and 3.5 L of activation solution are added to a reactor and stirred. The temperature of the reactor is raised to 75°C, and the mixture is stirred for 45 minutes. The temperature of the reactor is lowered to room temperature, and the filter cake is filtered and washed with purified water until it is neutral and then dried. The filter cake is transferred to a drying oven at 75°C and dried to constant weight to obtain activated microspheres. Weigh: 500 g of activated microbeads, 200 g of 7-octenyltrimethoxysilane and 3 L of anhydrous ethanol, add them into a reactor and stir, raise the temperature of the reactor to 55°C, add 800 mL of 1.0 mol / L sodium hydroxide solution into the reactor, keep warm and react for 90 min, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral and then dry, transfer the filter cake to a drying oven at a temperature of 70°C, and vacuum dry it to constant weight to obtain modified glass microbeads.
[0041] S4. Preparation of modified CM materials The modified inorganic powder and the modified glass microspheres are uniformly mixed in a weight ratio of 5.5:3.5 to obtain a composite filler; Dicumyl peroxide, zinc stearate, antioxidant 168, dioctyl phthalate and oleamide are uniformly mixed in a weight ratio of 10:3:4:5:3 to obtain an additive; Weigh: 9.5 kg of chlorinated polyvinyl chloride, 2.7 kg of modified chlorinated polyethylene rubber and 600 g of additives, add them to an internal mixer at a temperature of 175°C, keep warm and mix for 13 minutes, add 1000 g of vinyl triethoxysilane to the internal mixer in batches, keep warm and mix for 7 minutes, add 5.5 kg of composite fillers to the internal mixer in batches, keep warm and mix for 25 minutes, cool and discharge, and crush to obtain a modified CM precursor; Dicumyl peroxide, vulcanizing agent TDDS and accelerator 808 were uniformly mixed in a weight ratio of 2:4:1 to obtain a vulcanizing aid; Weigh: 10 kg of modified CM precursor, 900 g of ammonium carbonate and 500 g of vulcanizing agent, mix them evenly and add them into a twin-screw extruder, the temperatures of the 6 temperature sections from the feed end to the discharge end of the twin-screw extruder are 260° C., 265° C., 265° C., 265° C., 270° C., the screw speed of the twin-screw extruder is 18 r / min, and the twin-screw extruder is melt-extruded into a molding mold having the same molding cavity as the modified CM square power bellows provided in Example 1, and the temperature is reduced and solidified to obtain a modified CM blank; The modified CM blank was placed in a vulcanization tank with a temperature of 165°C and a pressure of 1.3 MPa. The vulcanization was carried out for 35 minutes to obtain a modified CM square power bellows. Example 4
[0042] A method for preparing a modified CM square power bellows in this embodiment comprises the following steps: S1. Preparation of modified chlorinated polyethylene rubber Weigh: 611.3 g of hexamethyl-1,15-dihydroxyoctasiloxane and 6113 mL of acetone, add them into a nitrogen-protected reactor and stir, add 494.7 g of isocyanatepropyltriethoxysilane into the reactor, raise the temperature of the reactor to reflux the system, react for 80 min, and evaporate the solvent under reduced pressure to obtain modified polysiloxane; Purified water, polyethylene glycol 400, and sodium dodecylbenzene sulfonate were mixed uniformly in a ratio of 100 mL:7 g:2 g to obtain an emulsion; Weigh: 1000g of chlorinated polyethylene rubber, 200g of modified polysiloxane, 120g of tetraethyl orthosilicate, and 5000mL of emulsion, add them into a high-speed dispersing emulsifier, emulsify and disperse, then transfer them to a reactor for stirring, raise the temperature of the reactor to 80°C, add hydrochloric acid to the reactor, adjust the pH of the system to 3, keep the reaction warm for 3h, lower the temperature of the reactor to room temperature, centrifuge, wash the solid with purified water until it is neutral, transfer it to a drying oven at 80°C, and vacuum dry it to constant weight to obtain modified chlorinated polyethylene rubber.
[0043] S2. Preparation of modified inorganic powder The attapulgite and kaolin are mixed uniformly in a weight ratio of 3:2 to obtain an inorganic mixed powder; Weigh: 700 g of inorganic mixed powder, 4 L of purified water and 300 g of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride, add them to a reactor, ultrasonically disperse for 50 min, raise the temperature of the reactor to 75° C., add 1 L of 2 mol / L sodium hydroxide solution to the reactor, keep warm and ultrasonic for 80 min, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral and then drain, transfer the filter cake to a drying oven at 80° C., and dry to constant weight to obtain intermediate I; Anhydrous methanol and purified water were mixed uniformly in a volume ratio of 3:2 to obtain a methanol solution; Weigh: 500 g of intermediate I and 5 L of methanol solution are added to the reactor, ultrasonically dispersed for 50 min, 500 g of sodium sulfate of nonylphenol polyoxyethylene ether (10) is added to the reactor, and ultrasonically dispersed for 8 h at room temperature. The temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed with purified water until it is neutral and then dried, the filter cake is transferred to a drying oven at a temperature of 80°C, and dried to constant weight to obtain a modified inorganic powder.
[0044] S3. Preparation of modified glass microspheres Mix hydrofluoric acid, 50 wt% nitric acid and purified water in a ratio of 0.5 mL:30 mL:50 mL to obtain an activation solution; Weigh: 500 g of hollow glass microspheres and 3.5 L of activation solution are added to a reactor and stirred. The temperature of the reactor is raised to 80°C, and the mixture is stirred for 50 min. The temperature of the reactor is lowered to room temperature, and the filter cake is filtered. The filter cake is washed with purified water until it is neutral and then dried. The filter cake is transferred to a drying oven at 80°C and dried to constant weight to obtain activated microspheres. Weigh: 500 g of activated microbeads, 200 g of 7-octenyltrimethoxysilane and 3 L of anhydrous ethanol, add them into a reactor and stir, raise the temperature of the reactor to 60°C, add 800 mL of 1.5 mol / L sodium hydroxide solution into the reactor, keep the reaction for 100 min, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral and then dry, transfer the filter cake to a drying oven at a temperature of 75°C, and vacuum dry it to constant weight to obtain modified glass microbeads.
[0045] S4. Preparation of modified CM materials The modified inorganic powder and the modified glass microspheres are uniformly mixed in a weight ratio of 6:4 to obtain a composite filler; Dicumyl peroxide, barium stearate, antioxidant 626, dimethyl phthalate and oleamide are uniformly mixed in a weight ratio of 10:3:4:5:3 to obtain an additive; Weigh: 10 kg of chlorinated polyvinyl chloride, 3 kg of modified chlorinated polyethylene rubber and 700 g of additives, add them to an internal mixer at a temperature of 180°C, keep warm and mix for 15 minutes, add 1200 g of vinyl triethoxysilane to the internal mixer in batches, keep warm and mix for 8 minutes, add 6 kg of composite fillers to the internal mixer in batches, keep warm and mix for 30 minutes, cool down, discharge, and crush to obtain a modified CM precursor; Dicumyl peroxide, vulcanizing agent TDDS and accelerator 808 were uniformly mixed in a weight ratio of 2:4:1 to obtain a vulcanizing aid; Weigh: 10 kg of modified CM precursor, 1000 g of ammonium carbonate and 600 g of vulcanizing agent, mix them evenly and add them into a twin-screw extruder, the temperatures of the 6 temperature sections from the feed end to the discharge end of the twin-screw extruder are 260° C., 265° C., 265° C., 265° C., 270° C., the screw speed of the twin-screw extruder is 18 r / min, and the twin-screw extruder is melt-extruded into a molding mold having the same molding cavity as the modified CM square power bellows provided in Example 1, and the temperature is reduced and solidified to obtain a modified CM blank; The modified CM blank was placed in a vulcanization tank with a temperature of 170°C and a pressure of 1.5 MPa. The vulcanization was performed for 40 minutes to obtain a modified CM square power bellows.
[0046] Comparative Example 1 The difference between this comparative example and Example 4 is that step S1 is eliminated, and the modified chlorinated polyethylene rubber in step S4 is replaced by the chlorinated polyethylene rubber in step S1.
[0047] Comparative Example 2 The difference between this comparative example and Example 4 is that in step S2, intermediate I is used to replace the modified inorganic powder in step S4.
[0048] Comparative Example 3 The difference between this comparative example and Example 4 is that in step S2, inorganic mixed powder is used to replace the modified inorganic powder in step S4.
[0049] Comparative Example 4 The difference between this comparative example and Example 4 is that step S3 is eliminated, and the hollow glass microspheres in step S3 are used to replace the modified glass microspheres in step S4.
[0050] Comparative Example 5 The difference between this comparative example and Example 4 is that in step S4, the vulcanizing agent TDDS is used instead of the vulcanizing aid.
[0051] Performance Test: The tensile yield stress and elongation at break of the modified CM square power bellows samples prepared in Examples 2-4 and Comparative Examples 1-5 were measured with reference to the standard GB / T8804.1-2003 "Determination of tensile properties of thermoplastic pipes Part 1: General principles of test methods"; The notched simply supported beam impact strength of the modified CM square power bellows samples prepared in Examples 2-4 and Comparative Examples 1-5 was measured at room temperature and -10°C in accordance with the standard GB / T 18743.1-2022 "Determination of simply supported beam impact strength of thermoplastic plastic pipes Part 1: General test method"; The burn-through time of the modified CM square power bellows samples prepared in Examples 2-4 and Comparative Examples 1-5 was measured with reference to the standard GB / T 25352-2010 "Test Method for Burn-through Resistance of Thermal and Sound Insulating Materials". The specific test results are shown in Table 1 below:
[0052] Data Analysis: Comparing and analyzing the data in Table 1 above, the tensile yield stress of the modified CM square power bellows prepared by the present invention reaches 48.86MPa, the elongation at break reaches 235.2%, the burn-through time reaches 78s, and the notched simply supported beam impact strength at room temperature reaches 18.6kJ / m 2 The impact strength of the notched simply supported beam at -15℃ is 16.8kJ / m 2 , all performance parameters are better than those of the comparative example; Data description: The present application is a composite mixed matrix of modified chlorinated polyethylene rubber and chlorinated polyvinyl chloride reinforced with siloxane, and a composite filler composed of modified inorganic powder and modified glass microspheres is used to reinforce the mixed matrix, which not only effectively enhances the tensile properties and impact resistance of the modified CM square electric bellows, but also improves the material's burn-through resistance and low-temperature resistance. Moreover, by optimizing the structure of the electric bellows, the modified CM square electric bellows is more convenient and has more advantages in practical applications.
[0053] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A modified CM square power bellows, characterized in that: It comprises a square tube and a plurality of corrugated rings arranged outside the square tube, wherein the square tube and the corrugated rings are both made of modified CM material; Two adjacent sides of the corrugated ring are provided with arc grooves; The modified CM material is processed by the following steps: A1. Add chlorinated polyvinyl chloride, modified chlorinated polyethylene rubber and additives to an internal mixer at a temperature of 170-180° C., keep warm and mix for 10-15 minutes, add vinyl triethoxysilane to the internal mixer in batches, keep warm and mix for 5-8 minutes, add composite fillers to the internal mixer in batches, keep warm and mix for 20-30 minutes, cool and discharge, and crush to obtain a modified CM precursor, wherein the composite filler is composed of modified inorganic powder and modified glass microspheres in a weight ratio of 5-6:3-4; A2, after uniformly mixing the modified CM precursor, ammonium carbonate and vulcanization aid, adding the mixture into a twin-screw extruder, molten-extruded into a molding die, cooling and solidifying, to obtain a modified CM blank; A3. Place the modified CM blank in a vulcanizing tank, vulcanize it under heat preservation to obtain a modified CM material.
2. A modified CM square power bellows according to claim 1, characterized in that: In step A1, the weight ratio of the chlorinated polyvinyl chloride, modified chlorinated polyethylene rubber, additive, vinyl triethoxysilane and composite filler is 90-100:25-30:5-7:8-12:50-60, the composite filler is composed of modified inorganic powder and modified glass microspheres in a weight ratio of 5-6:3-4, and the additive is composed of initiator, dispersant, antioxidant, plasticizer and lubricant in a weight ratio of 10:3:4:5:3; in step A2, the weight ratio of the modified CM precursor, ammonium carbonate and vulcanization aid is 100:8-10:4-6, and the vulcanization aid is composed of diisopropylbenzene peroxide, vulcanizing agent TDDS and accelerator 808 in a weight ratio of 2:4:1; in step A3, the temperature of the vulcanization tank is 160-170°C, the pressure is 1.2-1.5MPa, and the vulcanization time is 30-40min.
3. The modified CM square power bellows according to claim 1, characterized in that: Modified chlorinated polyethylene rubber is processed by the following steps: B1. Hexamethyl-1,15-dihydroxyoctasiloxane and acetone are added to a nitrogen-protected reactor and stirred. Isocyanatepropyltriethoxysilane is added to the reactor. The temperature of the reactor is raised to reflux, and the reaction is carried out for 60-80 minutes. The modified polysiloxane is obtained by post-treatment. B2. Add chlorinated polyethylene rubber, modified polysiloxane, tetraethyl orthosilicate and emulsion into a high-speed dispersing emulsifier, and then transfer to a reactor for stirring. The temperature of the reactor is increased to 70-80°C. Hydrochloric acid is added to the reactor to adjust the pH value of the system to 2-3. The reaction is kept warm for 2-3 hours, and the modified chlorinated polyethylene rubber is obtained by post-treatment.
4. The modified CM square power bellows according to claim 3, characterized in that: In step B1, the dosage ratio of hexamethyl-1,15-dihydroxyoctasiloxane and isocyanatepropyltriethoxysilane is 1 mol:2 mol, and the dosage ratio of hexamethyl-1,15-dihydroxyoctasiloxane and acetone is 1 g:10 mL; in step B2, the dosage ratio of the chlorinated polyethylene rubber, modified polysiloxane, tetraethyl orthosilicate, and emulsion is 8-10 g:1-2 g:0.8-1.2 g:50 mL, and the emulsion is composed of purified water, polyethylene glycol 400, and sodium dodecylbenzene sulfonate in a dosage ratio of 100 mL:7 g:2 g.
5. The modified CM square power bellows according to claim 1, characterized in that: The modified inorganic powder is processed by the following steps: C1. Mixing attapulgite and kaolin to form an inorganic mixed powder; C2, adding the inorganic mixed powder, purified water and dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride into a reactor, ultrasonically dispersing for 30-50 min, raising the temperature of the reactor to 67-75° C., adding sodium hydroxide solution into the reactor, keeping the temperature and ultrasonically dispersing for 60-80 min, and post-treating to obtain intermediate I; C3. Add intermediate I and methanol solution into a reactor, and disperse them by ultrasonic for 40-50 min. Add sodium sulfate of nonylphenol polyoxyethylene ether (10) into the reactor, and disperse them by ultrasonic for 6-8 h at room temperature. Post-treat to obtain modified inorganic powder.
6. The modified CM square power bellows according to claim 5, characterized in that: In step C1, the weight ratio of the attapulgite and kaolin is 3:2; in step C2, the amount ratio of the inorganic mixed powder, purified water, dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride and sodium hydroxide solution is 7g:40mL:3g:10mL, and the concentration of the sodium hydroxide solution is 1-2mol / L; in step C3, the amount ratio of the intermediate I, the methanol solution and nonylphenol polyoxyethylene ether (10) sodium sulfate is 10g:100mL:10g, and the methanol solution is composed of anhydrous methanol and purified water in a volume ratio of 3:
2.
7. The modified CM square power bellows according to claim 1, characterized in that: The modified glass microspheres are processed by the following steps: D1. Add hollow glass microspheres and activation solution into a reaction kettle and stir. Raise the temperature of the reaction kettle to 70-80°C, keep warm and stir for 40-50 minutes, and perform post-treatment to obtain activated microspheres. D2. Add activated microbeads, 7-octenyltrimethoxysilane and anhydrous ethanol into a reactor and stir. Increase the temperature of the reactor to 50-60° C., add sodium hydroxide solution into the reactor, keep the temperature for 80-100 minutes, and perform post-treatment to obtain modified glass microbeads.
8. The modified CM square power bellows according to claim 7, characterized in that: In step D1, the hollow glass microspheres and the activation solution are used in a ratio of 1 g:7 mL, and the activation solution is composed of hydrofluoric acid, 50 wt% nitric acid and purified water in a ratio of 0.5 mL:30 mL:50 mL; in step D2, the activated microspheres, 7-octenyltrimethoxysilane, anhydrous ethanol and sodium hydroxide solution are used in a ratio of 5 g:2 g:30 mL:8 mL, and the concentration of the sodium hydroxide solution is 0.5-1.5 mol / L.
Citation Information
Patent Citations
Modified chlorinated polyvinyl chloride cable protective double-layer corrugated pipe and preparation method thereof
CN105802094A
Flame-retardant rubber and plastic thermal insulation foaming material and preparation method thereof
CN110655695A
Composite heat stabilizer, chlorinated polyvinyl chloride pipe and preparation method of chlorinated polyvinyl chloride pipe
CN112812374A
Preparation method of chlorinated polyethylene with high elongation at break
CN118459902A
Block chlorinated polyolefins for use as impact modifier enhancers for PVC or CPVC
CN1376177A
Cited By
Reinforced and toughened CM square electric corrugated pipe and preparation method thereof
CN122011593A